KayKama Enterprise / Nur Asyiqin Sharudin, Najwa Izzati Mohd Zahid, Nur Farahuda Ramlan, Hany Marissa Badrul Sham and Nadiah Mohd Salikhin - Sharudin, Nur Asyiqin; Mohd Zahid, Najwa Izzati; Ramlan, Nur Farahuda; Badrul Sham, Hany Marissa; Mohd Salikhin, Nadiah (2019)
Instant noodle has been one of the most popular food in Malaysia especially among university students. Instant noodle is made up of wheat flour, palm oil, and salt. It is usually being sell in a dried noodle block, with flavouring powder that is usually in a separate packet.